SIMILARITIES AND DIFFERENCES OF NUMBER OF NOUN IN ENGLISH AND RUSSIAN LANGUAGES - Odilova Mashkhura; Aziz Mukhammadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: The category of noun "number" is a fundamental aspect of grammar that plays a crucial role in language structure and communication. Number refers to whether a noun is singular, representing one person, place, thing, abstract thing or idea, or plural, indicating more than one. Understanding noun number is essential for constructing grammatically correct sentences, as it influences verb agreement, pronoun reference, and overall sentence structure. This article aims to explore the perspectives of both English and Russian scholars on this linguistic phenomenon. By delving into relevant theories and drawing upon examples from English and Russian literature, we are about to compare and contrast the terminologies and approaches employed in each language.